(untitled) - Hamilton, Linda H. (San Francisco, CA, 1998)
The book is filled with answers to dancer's most often asked questions and offers practical methods for dealing with such difficult problems as eating disorders, substance abuse, ruthless competition, and performance anxiety. Advice for Dancers will teach you how to: Achieve you physical potential and select the dance technique that's right for you, Find out which teaching practices you can trust and why, Learn how to reach your optimal weight without compromising your energy, health, and career, Develop healthy relationships both inside and outside the dance studio, Use a variety of resources to get work, roles, and promotions Perform technical feats in front of an audience even when you are frightened
Keywords: Dance,Dance; Psychological aspects,Vocational guidance